Derivation of the characteristic water pressure resistance of combined steel pile walls. Issue 1 (8th February 2018) - Just, Adrian; Kuhlmann, Ulrike; El Boueiz, Perla; Prüm, Cécile
Abstract: World trade is steadily increasing, leading to a high demand for economic solutions for quay walls. The combined steel pile wall is the most common steel construction solution. The primary elements are king piles, while intermediate piles function as secondary elements. The design of these secondary elements is governed by section 5.5.2 of EN 1993‐5 [9]. The test‐based method described in section 5.5.2(5) and (6) is used to generate the characteristic water pressure resistance values of the different combinations of I‐shaped king and Z‐shaped intermediate piles, each in different steel grades, which are given in the product catalogue of ArcelorMittal [1]. The test series executed and the subsequent setting‐up and validation of a numerical model are presented in detail in this paper. A numerical model was used for a parametric study. The different failure modes observed in this parametric study are presented. A statistical evaluation according to Annex D of EN 1990 [6] and Annex C of EN 1993‐1‐5 [8] leads to characteristic resistance values.